2013
DOI: 10.1186/1477-7517-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Should North America’s first and only supervised injection facility (InSite) be expanded in British Columbia, Canada?

Abstract: BackgroundThis article reports qualitative findings from a sample of 31 purposively chosen injection drug users (IDUs) from Vancouver, Surrey and Victoria, British Columbia interviewed to examine the context of safe injection site in transforming their lives. Further, the purpose is to determine whether the first and only Supervised injection facility (SIF) in North America, InSite, needs to be expanded to other cities.MethodsSemi-structured qualitative interviews were conducted in a classical anthropological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 11 publications
1
67
0
2
Order By: Relevance
“…The contraction and spread of HIV via People Who Inject Drugs (PWID) is not a problem exclusive to large cities and urban areas as small and medium sized towns have reported an increase in HIV infection (1). The Downtown Eastside (DTES) of Vancouver has historical shared similarities with many small cities in Canada in terms of HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…The contraction and spread of HIV via People Who Inject Drugs (PWID) is not a problem exclusive to large cities and urban areas as small and medium sized towns have reported an increase in HIV infection (1). The Downtown Eastside (DTES) of Vancouver has historical shared similarities with many small cities in Canada in terms of HIV prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Other outreach centers across Canada provide access for marginalized populations to obtain harm reduction supplies, which essentially include clean needles, condoms, food, water, and telephone access (Krusi et al, 2012 Vancouver in 2003, has resulted in a decrease in the incidents of overdoses and the transmission of blood-borne diseases, and, an increase the retention rates for people in detox and treatment facilities, along with an increase in the exposure of the marginalized population to the health care system (Small, 2012). It has also been shown that the InSite program has resulted in a reduction in injections taking place in public places, has kept dirty needles off the streets, and has reduced the use of emergency services, while increasing access to health care providers (namely nurses) and other resources, and generally keeping people alive (Jozaghi & Andresen, 2013).…”
Section: Outreach Servicesmentioning
confidence: 99%
“…Eight studies using data relating to British Columbia have been reviewed (Deering et al, 2011a;Janssen et al, 2009;Jozaghi & Andresen, 2013;Kurtz et al, 2008;Lazarus et al, 2012;Marshall et al, 2005;Salmon et al, 2009;Wardman, Clement, & Quantz, 2005). Four studies from Ontario were identified and included (Butters & Erickson, 2003;Daiski, 2005;Goodman, 2006;Woolhouse, Brown, & Lent, 2004).…”
Section: Chapter Four Findingsmentioning
confidence: 99%
See 2 more Smart Citations